Implementation of the Al-'Adad wal Ma'dud Rule in Improving the Maharah Kitabah with Image Media in Class XI of Tahfidzu Al-Qur'an Vocational School Umbulsari Jember. - Nafsah, Nor Holis bin; Khoiroh, Immatul; Ghofur, M. Abdul; Sholehudin, Moch (Al-Fusha : Arabic Language Education Journal, 2025)
Of the several skills developed in Arabic, communication skills via writing also need to be deepened, considering the importance of this skill as a channel of information, knowledge and other things. However, this Mahroh Kitabah is a fairly difficult skill level for Arabic language students. This research aims to determine the effectiveness of learning Al-'adad wal ma'dud rules using image media on students' writing skills in Arabic language subjects at Tahfidzu Al-Qur'an Vocational School Umbulsari Jember. This research uses qualitative methods with data collection techniques through observation, interviews and documentation. The results of the research show that the implementation of counting in Arabic using picture media has proven to be effective and can improve students' Arabic numeral writing skills. This is proven by 85% of students experiencing significant development, and 10% are considered sufficient, while 5% need further guidance.